M32 - PER3 POLYMORPHISMS, MORNINGNESS-EVENINGNESS AND DEPRESSION: PRELIMINARY EVIDENCE IN A BRAZILIAN FAMILY-BASED COHORT, THE BAEPENDI HEART STUDY - Ruiz, Francieli; P. Taporoski, Tâmara; Martinez, Daniela; Beale, Andrew; Beijamini, Felipe; Krieger, José E.; Knutson, Kristen L.; Pereira, Alexandre; Pedrazzoli, Mario; Vallada, Homero; Von Schantz, Malcolm (European neuropsychopharmacology, 2019)
There is a significant interest in the contribution of the circadian timing system to individual differences in a wider range of behaviour. This is in part because sleep complaints and disturbances of the circadian timing system are common in psychiatric disorders. Based on diurnal preference, people can be divided into chronotypes with demonstrated differences in sleep-wake patterns and a variety of circadian rhythms, behavioral rhythms, and diurnal variation in mood. Specifically, greater eveningness has been related to greater depression. The human PER3 gene contains a variable number tandem repeat (VNTR) which is associated with diurnal preference: the longer allele (five tandem repeats) has been reported to associate with greater morningness, and the shorter allele (four tandem repeats) with greater eveningness. We have investigated the PER3 polymorphism and its relationship to sleep, circadian and depression characteristics in a Brazilian family-based cohort. Baependi is a small rural town in Brazil that provides a window of opportunity to study the influence of sleep circadian patterns in a highly admixed rural population with a conservative lifestyle. Here, we studied 786 subjects (mean age±SD 46.5±16.2, 42% female). Blood samples were collected from all participants. The Per3 length polymorphism was genotyped using PCR followed by gel electrophoresis. We tested for associations between the PER3 polymorphism and sleep characteristics, daytime sleepiness, and chronotype using the Pittsburgh Sleep Quality Index, Epworth Sleepiness Scale and Morningness-Eveningness Questionnaire, respectively. Depressive symptoms were assessed using the Beck Depression Inventory [BDI-II]). Our genotyping data showed that 36% of the subjects were homozygous for the shorter allele (4/4), 51% of the participants were heterozygous (4/5) and 12% of the subjects were homozygous for the longer allele (5/5). Allele frequency was 0.62 for the 4-repeat and a 0.38 for the 5-repeat. The percentages of the chronotypes Morning type (M-type), Neither type (N-type) and Evening type (E-type) were 5%, 46% and 7%, respectively. We observed an increase of the depression symptoms in evening types [F(2, 1014)=4.8, p=0.007]. On the other hand, no such associations were observed the PER3 genotype. There were no significant differences in the MEQ score [F(2, 317)=0.46, p=0.63], daytime sleepiness [(F(2, 317)=0.23, p=0.79)], sleep efficiency [(F(2, 317)=2.59, p=0.07)] and sleep characteristics [(F(2, 317)=1.92, p=0.14)] between the PER3 genotypes. We observed an association between eveningness and depression. Identifying factors contributing to individual differences in sleep and to describe how these factors are associated with physiological and psychological profiles may aid our understanding of the role of sleep and the circadian system in mental health. On the other hand, we were not able to replicate the association between the PER3 VNTR polymorphism and chronotype, which has been confirmed independently in multiple populations worldwide (including in Brazil). Neither did we observe any association with depression. CNPq – PVE 400791/2014-5.